2021
DOI: 10.1016/j.jare.2020.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Role of hydrogen sulfide in endothelial dysfunction: Pathophysiology and therapeutic approaches

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 162 publications
(190 reference statements)
1
69
0
Order By: Relevance
“…Altered levels of H 2 S have been reported in both experimental models and clinical studies on patients with severe hypertension, where lower plasma H 2 S levels are described along with reduced content of CBS and CSE (see [ 77 , 78 ] for recent reviews). A human cohort study demonstrated a reduced H 2 S plasma level in hypertensive patients, suggesting H 2 S as a potential therapeutic target and diagnostic marker [ 79 ].…”
Section: Cardiovascular Diseases Associated With Altered Levels Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered levels of H 2 S have been reported in both experimental models and clinical studies on patients with severe hypertension, where lower plasma H 2 S levels are described along with reduced content of CBS and CSE (see [ 77 , 78 ] for recent reviews). A human cohort study demonstrated a reduced H 2 S plasma level in hypertensive patients, suggesting H 2 S as a potential therapeutic target and diagnostic marker [ 79 ].…”
Section: Cardiovascular Diseases Associated With Altered Levels Ofmentioning
confidence: 99%
“…The relation between diabetes-induced endothelial dysfunction and H 2 S impairment is now well established (for review see [ 77 , 97 ]). H 2 S levels have been observed to be reduced in rats with diabetes induced by streptozotocin (STZ) and in subjects with type 2 diabetes mellitus [ 98 , 99 , 100 , 101 , 102 ].…”
Section: Cardiovascular Diseases Associated With Altered Levels Ofmentioning
confidence: 99%
“…Nrf-2 is accountable for inducing the expression of multiple antioxidant genes and averting oxidative injury. This kind of mechanism of action has also been defined for synthetic thiocyanate, whose H 2 S donor profile has been extensively discussed [ 147 , 165 , 166 , 167 , 168 , 169 , 170 , 171 ]. Anethiole dithiolethione has often been an H 2 S donor or a compound for developing H 2 S-releasing hybrid drugs with the non-steroidal anti-inflammatory agents H 2 S-diclofenac and H 2 S-aspirin.…”
Section: H 2 S In Pulmonary Inflammationmentioning
confidence: 99%
“…Reduced levels of H 2 S have been found in patients with acute or stable coronary artery disease [ 158 ], hypertension [ 159 ], and heart failure [ 160 ]. The impact of H 2 S on cardiovascular disease has been extensively updated and reviewed in recent studies [ 161 , 162 , 163 , 164 , 165 ].…”
Section: H 2 S On Cardiovascular Diseasementioning
confidence: 99%